An outbreak of acute postoperative endophthalmitis after cataract surgery - Sakarin Ausayakhun (2018)
Background: Endophthalmitis is one of the most serious complications of ophthalmic surgery, which includes postoperative cataract extraction. Outbreak of acute postoperative endophthalmitis after cataract surgery has been reported in Thailand and other countries. Objective: To describe an outbreak of acute postoperative endophthalmitis after cataract surgery that was referred to Chiang Mai University Hospital during March 2006. Material and Method: Observational case series were made from the records of inpatients and outpatients, who had been referred for treatment of acute postoperative endophthalmitis after cataract surgery at a district hospital in northern Thailand. The surgery was conducted on two consecutive days by volunteer ophthalmologists of a non-profit foundation from Bangkok. Results: In this outbreak, the authors recorded 31 endophthalmitis cases, with 33 eyes (bilateral 2 cases). Of the 33 endophthalmitis eyes, 32 occurred following extracapsular cataract extraction with intraocular lens and one after the secondary intraocular lens implant. Microbiological investigations in the hospital were done with aqueous tapping, vitreous tapping, and vitreous from pars plana vitrectomy. Gram-positive cocci were detected from vitreous tapping in four eyes. Thirty-two cases were managed with intravitreous antibiotics, one with subconjunctival antibiotic only, and all eyes were treated with fortified topical antibiotics. Fifteen eyes underwent pars plana vitrectomy. Assessment of visual acuity (VA) before and after treatment showed improvement in 75.8% (25/33), decrease of VA in 9.1% (3/33), while visual acuity remained stable in 15.2% (5/33). Conclusion: In high-volume cataract surgery, an outbreak of endophthalmitis is always possible. Prompt and appropriate treatment can improve the visual outcome.